STUDI FENOMENOLOGI: PENGALAMAN MANTAN PENGGUNA NAPZA TENTANG PEMAKAIAN NAPZA DI WILAYAH KERJA PUSKESMAS ANDALAS KEL. ANDALAS KEC. PADANG TIMUR PADANG - Jumilia Jumilia; Achir Yani S. Hamid; Ira Erwina (Ensiklopedia of Journal, 2023)
Drug could be ruin psycal and psycologhical, drug also in close related to criminal and violence. Drug could be misused by people whose addicted. Misused of drug was out of under medic indication using, not under doctor receipes and have patology impact. This research aim to know the experience of drug addicted about drud comsumed at kelurahan andalas kecamatan andalas Padang City. This is qualitative research with fenomenology design. Participants of thise research chosen by snowball methode. 6 participant are have drug addict curriculum. This research has result 11 themes that are; first reason Initial progres fells banded to drug, type of drug wich consumed, how to got it, body response, psycologic response during consume it, behavior response during consumed, concequense reflection that happen, response of parent, encourage of decide to stop consumed it, and source of support. Researcher conclude, drug addicted able to stop consumed by own self strong motivation and supported by family support, best friends, and medical team. Support also needed to develope health of environment make a supporting group. Be expected to nurse at puskemas could empower family to create self help group.